Incidence and risk factors for psychological distress in adult female patients with breast cancer: a systematic review and meta-analysis - Tao, Lin; Xiang, Yuping; Zeng, Xiaohong; Fu, Lan; Li, Junying; Chen, Hong (Frontiers in Psychiatry, 2024)
Introduction: Cancer-related distress can be described as a complex and unpleasant combination of psychological (such as cognitive, behavioral, and emotional), social, and spiritual challenges that may impact an individual's ability to effectively cope with the physical symptoms of cancer and its treatment. Existing literature has confirmed psychological distress (PD) as an important sequela of breast cancer diagnosis and treatment. However, the incidence and risk factors for PD in adult female patients with breast cancer remain unclear; therefore, focusing on the PD of female breast cancer patients is meaningful, as they are at highest risk of contracting breast cancer, and might differ in their coping styles from men. Objective: This review aimed to identify the incidence and risk factors for PD in adult woman patients with breast cancer, and to help guide targeted intervention to prevent distress. Method: PubMed, Embase, Cochrane Library, CINAL, PsycINFO, China Knowledge Resource Integrated Database, Wanfang Database, the Chinese Biomedical Database, and Weipu Database were searched for data regarding the incidence and risk factors of PD in adult women with breast cancer. Results: The prevalence of PD, assessed using the distress thermometer, ranged between 11.2%–86.7%, and a meta-analysis of 47 studies with 15,157 adult female breast cancer patients showed that the pooled prevalence was 52.0%. Further, this study identified 40 risk factors. However, owing to the inclusion of at least two studies for a certain risk factor, 10 risk factors were merged for the meta-analysis. Independent risk factors included higher education level, late-stage tumor, emotional concerns, no medical insurance, modified radical mastectomy, and history of depression; age and neuroticism were not associated with PD; and higher monthly income was revealed as a protective factor against it. Conclusion: The incidence of PD in female patients with breast cancer is high and it involves 10 risk factors, though some are controversial owing to insufficient evidence. Further research is needed to explore the underlying mechanisms of PD and develop risk factor-based holistic intervention programs to reduce its incidence.